Studi Anteseden Intensi Berwirausaha Mahasiswa - Woro Endah Sulistyaningrum; Majang Palupi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2016)
In this research, theory of planned behavior in order to understand the entrepreneurial intention students by looking at the effects of attitude toward entrepreneurial behavior, subjective norms and self efficacy. Respondents of this research were 400 students of state university in Indonesia. Data is analyzed by multiple regression analysis. The result showed that attitude variable, subjective norm and self efficacy are affecting entrepreneurial intention. Analysis result showed that subjective norm were the most significant effect toward entrepreneurial intention.